Survey: A Public Preference for Home Care - Don Guy (Healthcare Quarterly, 2002)
A couple of years ago I wrote a column for this publication regarding public opinion on home care. That column reviewed the evolution of the public's views, concluding on an optimistic note that ... "The home care debate is indeed maturing in Canadian public opinion. As problems in emergency and acute care settings are dealt with, the public will begin to demand increased attention to issues such as home care, not at the expense of hospitals, but as part of an integrated continuum of care that can improve the health outcomes of discharged hospital patients." Since that time, the research that we have conducted for the Romanow Commission, through our Health Care in Canada annual series, and for Health Canada has confirmed the public's preferences for home care. And now home care has been placed squarely in the middle of the medicare reform debate, in part because Canadians express almost universal support for the federal government working with the provinces to fund a national home care program (92%; including 57% who strongly support.) Home care has risen steadily in recent years to become the most popular of potential new directions in medicare reform.